Analisis Kualitas Produk untuk Meningkatkan Kepuasan Nasabah - Agus Wahyu Irawan (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
The purpose of this article is to find out how to optimize product quality for customer satisfaction. The type of data used in this article is secondary data. Secondary data is data obtained from library sources which include documents, books, and research reports. How to optimize product quality by means of initial ideas or ideas, screening of ideas or ideas, concept development and testing, marketing strategies, business analysis, product development, market testing, commercialization. Product quality is something that provides benefits both in terms of meeting daily needs or something that consumers want to have. Therefore, good product quality will affect customer satisfaction.